Transcriptome Analysis of Aureobasidium pullulans YQ65 Grown on Yeast Extract Peptone Glucose and Potato Dextrose Agar Media and Quantification of Their Effects on Pullulan Production - Wan Wang; Jiyun Zhao; Kai Zhang; Zhengran Wang; Jingqiu Ma; Qian Yang; Congyu Lin (Foods)
Pullulan is a high-value polysaccharide produced through the fermentation of Aureobasidium pullulans. It has significant applications in the fields of food, medicine, environmental science, and packaging. However, the yield, molecular weight, and other characteristics of pullulan can vary depending on the fermentation substrate used. Therefore, it is crucial to analyze the underlying causes of these variations at the molecular level. In this study, we first investigated the morphological differences in A. pullulans YQ65 when cultured in YPD and PDA media. The results indicated that different culture media significantly influence the primary cell morphology of A. pullulans YQ65, which in turn affects the synthesis of secondary metabolites. Subsequently, we employed different culture media to ferment pullulan and examined the variations in pullulan yield, molecular weight, and biomass. Moreover, FTIR and thermodynamic stability tests were conducted to analyze the differences among pullulans across different culture media. Finally, transcriptome analysis revealed that A. pullulans YQ65, when cultured in YPD and PDA media, regulates its growth and metabolism through the expression of key genes that are involved in pathways such as the proteasome, oxidative phosphorylation, metabolism of various secondary metabolites, fatty acid anabolism, carbon metabolism, and amino acid metabolism. The transcriptome results were further validated by assessing the expression of specific genes. This study enhances the understanding of the fermentation differences observed with different substrates in A. pullulans and provides valuable insights for optimizing culture substrates. Additionally, it offers guidance for utilizing agricultural and forestry processing waste, as well as food processing by-products, to produce pullulan cost-effectively in the future.